Odpowiedzi

2010-03-08T19:15:00+01:00
A)
a=3
h=a pierwiastki z 3/2
h=3 pierwiastki z3/2
h=1,5 pierwiastek z3
Pp=a razy h/2
Pp= 3 razy 1,5 pierwiastek z 3/2=2,25 pierwiastek z 3
H=8
V=Pp razy H
v= 2,25 pierwiastek z 3 razy 8=18 pierwiastek z 3
b)
H=6
a=4
h=3
Pp= a razy h/2
Pp= 4 razy 3 /2
Pp=6
V=Pp razy H
V= 6 razy 6 =36
c)
H=9
a=3
b=7
h=3
Pp=(a+b) razy h/2
Pp=10 razy 3/2
Pp=15
V=Pp razy H
V= 15 razy 9
V= 135
1 5 1
Najlepsza Odpowiedź!
2010-03-08T19:27:13+01:00
A) H=8
Podstawa to trójkąt równoboczny
V= 3²√3 /4 *8
V=9√3 /4 *8
V=18√3

b) H=6
Pp=a*h/2
Pp=3*4/2
Pp=6
V=Pp*H
V=6*6
V=36

c) H=9
Pp=(a+b)*h /2
Pp=(3+7)*3 /2
Pp=30/2
Pp=15
V=15*9
V=135
1 1 1